Impact of corporate social responsibility on brand equity at Citibank N.A. Bangladesh - Keya, Ishita Hossain (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.